Designing 'Totem' C2‐Symmetrical Iron Porphyrin Catalysts for Stereoselective Cyclopropanations. Issue 38 (24th August 2016) - Carminati, Daniela Maria; Intrieri, Daniela; Caselli, Alessandro; Le Gac, Stéphane; Boitrel, Bernard; Toma, Lucio; Legnani, Laura; Gallo, Emma
Abstract: The catalytic activity of the iron(III) C2 chiral porphyrin Fe(2 )(OMe) in alkene cyclopropanation is herein reported. The catalyst promoted the reaction of differently substituted styrenes with diazo derivatives with trans ‐diastereoselectivities and enantioselectivities up to 99:1 and 87 %, respectively. In addition, high TON and TOF values (up to 10 000 and 120 000 h −1, respectively) were observed indicating good activity and stability of the catalyst in optimized experimental conditions. The study of the cyclopropanation reaction revealed that the porphyrin skeleton is composed of two ' totem ' parts which were independently responsible for the observed enantio‐ and diastereoselectivities. To further our research we also investigated the catalytic role of the methoxy axial ligand coordinated to the iron atom. The molecular structure of Fe(2 )(OMe) was optimized by DFT calculations which were also employed to achieve a better understanding of the mechanistic details of the carbene transfer reaction. Abstract : Distinct regions : The activity of an iron(III) C 2 chiral bis‐strapped porphyrin catalyst to promote the cyclopropanation of differently substituted styrenes by diazo derivatives is herein reported. Good stereoselectivities (up to 87 % ee and 99:1 d.r. trans ) and high TON and TOF values (up to 10 000 and 120 000 h −1, respectively) were achieved. A DFT study was also performed to investigate some mechanistic aspects of the catalytic reaction.